Pengaruh Metode Storytelling Terhadap Penanaman Karakter Nasionalisme Pada Siswa SD - Ruwet Rusiyono; An-Nisa Apriani (LITERASI (Jurnal Ilmu Pendidikan), 2020)
This research is motivated by a phenomenon that exists in the world of education today, namely the lower values of national character inherent in students. This is because teachers still rarely insert nationalistic values in learning activities. For that we need the right way to incorporate the values of nationalism character in learning using interesting learning methods so as to create student enthusiasm for learning. This study aims to determine the effect of storytelling methods on the cultivation of nationalism in elementary school students. This research uses a quantitative approach with an experimental method. The research subjects were grade V students of Ngebel Elementary School, Kasihan, Bantul. Data collection techniques used were interviews, observation and documentation. Based on the results of pre-test and post-test data processing, the t-test calculation through the SPSS program with the results of the inculcation of nationalism in children carried out before and after the treatment is a t-count of -11,393 with a Sig level, (2 tailed = 0,000 so the t table value of -2, 214 at the level of Significance (a = 0.05), because t-count ³ t table. Based on these results can be concluded that the storytelling method influences the planting of the character of nationalism in children.Keywords: storytelling, planting characters, nationalism